Consultation and Collaboration to Develop and Implement Restorative Practices in a Culturally and Linguistically Diverse Elementary School. Issue 4 (1st October 2016) - Ingraham, Colette L.; Hokoda, Audrey; Moehlenbruck, Derek; Karafin, Monica; Manzo, Caroline; Ramirez, Daniel
ABSTRACT: Through an embedded single-case study design and qualitative methods, this article describes the school-wide implementation and preliminary results of a restorative practices (RP) program within a culturally and linguistically diverse (CLD) elementary school. Located in an urban area with high rates of crime, violence, and poverty, the three-year multisystemic project brought school psychology knowledge and skills to (a) use multicultural consultation and participatory methods to introduce, adapt, and support RP in a CLD school, (b) present findings related to teachers, parents, students, and school climate, and (c) increase youth, parent, and community engagement and voice. The authors developed a comprehensive, culturally relevant model through an interdisciplinary school-university-community partnership. They used multicultural consultee-centered consultation, including bilingual/bicultural practices and cultural brokers, and participatory culture-specific intervention methods to collaboratively design, implement, and evaluate outcomes for students, parents, teachers, and others.